Perencanaan Strategi Bisnis dengan Penerapan Corporate Entrepreneurship dalam Meningkatkan Kinerja Perusahaan Studi Empiris Pada : UKM Industri Pakaian Jadi Kota Bekasi - Enny Diah Astuti (JURNAL LENTERA BISNIS, 2019)
This study analyzes the business strategy planning with corporate entrepreneurship. The scope of the issues examined in this study is the discussion in the planning of business strategy with the implementation of corporate entrepreneurship in improving company performance. This study in an empirical study of small and medium scale clothing industry in Bekasi. Thoseare 135 industries. Total sample in this research are 107 industries. Collecting data using questionnaires, while an analytical tool used is a structural equation modeling (SEM). The result of data analysis showed that this research model with acceptable goodness of fit. In general the conclusion from the results of model testing is applied to the apparel industry of small and medium scale in calculate showed that a good business strategy planning with implementation of corporate entrepreneurship to enhance corporate performance. This research has given some research limitation and also give agenda for next research.Keywords : strategy business, corporate, entrepreneurship